136k views
5 votes
What is the result of substituting for y in the bottom equation?

y = x – 7
y = x^2 + 2x – 4

A. x – 7 = x^2 + 2x – 4
B. y = (x – 7)^2 + 2(x – 7) – 4
C. x – 7 = x^2
D. y = x^2 + 2x – 4 – (x – 7)

2 Answers

2 votes

Answer:

A. x – 7 = x^2 + 2x – 4

Explanation:

Ap3x

User Melinath
by
5.9k points
3 votes
The answer is the option A, which is: A. x-7=x²+2x-4
The explanation is shown below:
To solve this problem you must apply the proccedure shown below:
1. You have the following system equations given in the problem above:
y=x-7
y=x²+2x-4
2. Therefore, when you substitute for y in the bottom equation, you obtain:
x-7=x²+2x-4
User Erikscandola
by
5.7k points